Plate vs. nail for extra-articular distal tibia fractures: How should we personalize surgical treatment? A meta-analysis of 1332 patients. Issue 3 (March 2021) - Bleeker, N.J.; van de Wall, B.J.M.; IJpma, F.F.A.; Doornberg, J.N.; Kerkhoffs, G.M.M.J.; Jaarsma, R.L.; Knobe, M.; Link, B.C.; Babst, R.; Beeres, F.J.P.
Highlights: Plate fixation and IMN are both viable treatment options for distal tibia fractures, each with its advantages and disadvantages. Intramedullary nailing is associated with a slightly increased risk of mal-union and anterior knee pain. Plating, however, results in a slightly higher rate of infection. The treatment of distal tibia fractures should, therefore, be based on a personalized approach and rely on shared decision-making. Abstract: Background: Treatment for distal diaphyseal or metaphyseal tibia fractures is challenging and the optimal surgical strategy remains a matter of debate. The purpose of this study was to compare plate fixation with nailing in terms of operation time, non-union, time-to-union, mal-union, infection, subsequent re-interventions and functional outcomes (quality of life scores, knee- and ankle scores). Methods: A search was performed in PubMed/Embase/CINAHL/CENTRAL for all study designs comparing plate fixation with intramedullary nailing (IMN). Data were pooled using RevMan and presented as odds ratios (OR), risk difference (RD), weighted mean difference (WMD) or weighted standardized mean difference (WSMD) with a 95% confidence interval (95%CI). All analyzes were stratified for study design. Results: A total of 15 studies with 1332 patients were analyzed, including ten RCTs ( n = 873) and five observational studies ( n = 459). IMN leads to a shorter time-to-union (WMD: 0.4 months, 95%CI 0.1 – 0.7), shorter time-to-full-weightbearing (WMD: 0.6 months, 95%CI 0.4 – 0.8) and shorter operation duration (WMD: 15.5 min, 95%CI 9.3 – 21.7). Plating leads to a lower risk for mal-union (RD: -10%, OR: 0.4, 95%CI 0.3 – 0.6), but higher risk for infection (RD: 8%, OR: 2.4, 95%CI 1.5 – 3.8). No differences were detected with regard to non-union (RD: 1%, OR: 0.7, 95%CI 0.3 – 1.7), subsequent re-interventions (RD: 4%, OR: 1.3, 95%CI 0.8 – 1.9) and functional outcomes (WSMD: -0.4, 95%CI -0.9 – 0.1). The effect estimates of RCTs and observational studies were equal for all outcomes except for time to union and mal-union. Conclusion: Satisfactory results can be obtained with both plate fixation and nailing for distal extra-articular tibia fractures. However, nailing is associated with higher rates of mal-union and anterior knee pain while plate fixation results in an increased risk of infection. This study provides a guideline towards a personalized approach and facilitates shared decision-making in surgical treatment of distal extra-articular tibia fractures. The definitive treatment should be case-based and aligned to patient-specific needs in order to minimize the risk of complications.